Scampi (Metanephrops challengeri) emergence patterns and catchability. (8th January 2015) - Tuck, Ian D.; Parsons, Darren M.; Hartill, Bruce W.; Chiswell, Stephen M.
Abstract: Catchability is often a key source of uncertainty with any stock assessment, but especially for burrowing species, as their emergent behaviour is often poorly understood. Quantification of catchability will provide a major step towards improvements in the assessment for many species. Scampi ( Metanephrops challengeri ) are widely distributed around New Zealand, and as with Nephrops (Norway lobster), they occupy burrows in muddy substrate, and are exploited through trawl fisheries, but are only available to these fisheries when emerged on the seabed. Burrow emergence is known to vary over daily and longer cycles. Uncertainty over trawl catchability associated with emergence patterns has led to the development of photographic survey approaches for scampi, based on the counts of burrows. Both survey approaches require an understanding of burrow occupancy and emergence rates to estimate trawl/photo survey catchability, which is a key source of uncertainty. We used acoustic tagging to examine levels of and patterns in the emergence of Metanephrops, using hydrophone receivers moored close to the seabed. Strong emergence cycles were apparent in relation to tidal current (higher emergence with inshore water flow across the slope) and time of day (peaking just after dawn). These data have subsequently been used within a length-based stock assessment of New Zealand scampi, which uses emergence data in conjunction with burrow and animal counts from photographic surveys, for the first time, to inform priors for trawl (mean 0.094) and photographic (mean 0.46) survey catchability, and for burrow occupancy (mean 49.3%).